Correction to: Geochemical characterization of fluoride in water, table salt, active sediment, rock and soil samples, and its possible relationship with the prevalence of enamel fluorosis in children in four municipalities of the department of Huila (Colombia) (2017)
Fluoride is an element that affects teeth and bone formation in animals and humans. Though the use of systemic fluoride is an evidence-based caries preventive measure, excessive ingestion can impair tooth development, mainly the mineralization of tooth enamel, leading to a condition known as enamel fluorosis. In this study, we investigated the geochemical characterization of fluoride in water, table salt, active sediment, rock and soil samples in four endemic enamel fluorosis sentinel municipalities of the department of Huila, Colombia (Pitalito, Altamira, El Agrado and Rivera), and its possible relationship with the prevalence of enamel fluorosis in children. The concentration of fluoride in drinking water, table salt, active sediment, rock, and soil was evaluated by means of an ion selective electrode and the geochemical analyses were performed using X-ray fluorescence. Geochemical analysis revealed fluoride concentrations under 15 mg/kg in active sediment, rock and soil samples, not indicative of a significant delivery to the watersheds studied. The concentration of fluoride in table salt was found to be under the inferior limit (less than 180 μg/g) established by the Colombian regulations. Likewise, exposure doses for fluoride water intake did not exceed the recommended total dose for all ages from 6 months. Although the evidence does not point out at rocks, soils, fluoride-bearing minerals, fluoridated salt and water, the hypothesis of these elements as responsible of the current prevalence of enamel fluorosis cannot be discarded since, aqueducts might have undergone significant changes overtime.